Re-Design of ESP Pump in EHS-155 Well in Tanjung Field Based on Problematic Scale and Economic Analysis - Hesmatiar, Ekwal; Herianto, Herianto; Budiharjo, Harry (Journal of Petroleum and Geothermal Technology, 2025)
The repair of Electric Submersible Pump (ESP) in well X-155 at the Tanjung Field has become a major issue impacting production rates and increasing operational costs. In 2024, well X-155 experienced 7 well service interventions due to pump failures, which caused damage to the pump impeller and resulted in a loss of oil production. This failure was identified as being caused by the deposition of carbonate minerals (scale), which became the primary cause of damage to the ESP pump. To confirm the presence of scale, solid scale deposition was analyzed using X-ray Diffraction (XRD) methods in an independent laboratory, along with fluid property testing. This method was used to determine the composition and crystalline phases of the scale formed in the well. This study aims to analyze the causes of scale formation in the ESP system. It is expected that the findings from this research will provide solutions to pump failures, reduce the frequency of such failures, and improve operational efficiency at the Tanjung Field, particularly through the implementation of scale inhibitor treatments. The scale treatment for well X-155 is unique due to the need to formulate a scale inhibitor that can function effectively under the high-temperature and high-pressure conditions present in the well